Functional-stylistic features of the repeat in the poetic texts of the late XX – early XXI century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article is devoted to the repeat as one of the dominant the of poetic language of the late XX – early XXI century. The attention is drawn to its «necessary assistance» from the other basic stylistic units. The author has analyzed the function of the repeat in the Ukrainian poetic texts of the specified period.
Keywords: poetic text; repeat; anaphora; epiphora; anepifora; gradation; amplification